STUDY OF PREDISPOSING FACTORS OF ALLERGIC RHINITIS IN SCHOOLCHILDREN (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Currently, the incidence of allergic rhinitis in the general population is 10–20%, and these figures tend to further increase this disease [1,5,6]. According to a number of epidemiological studies conducted in different regions of the world, the prevalence of AR in the pediatric population reaches 22%. It is especially common in children aged 3 to 16 years [6]. The disease limits the life of children, reduces their social and physical activity [6].